Prinsip dan Tujuan Penilaian Tindakan Kelas - Nurhayati, A. (Inspiratif Pendidikan, 2016)
Classroom Assessments are conducted in various ways, such as a written test (Paper and Pencils), students' work assessment through the ability of students’ work (portfolio), three-dimensional product assessment, and students’ performance assessment (performance). Classroom assessment is a process conducted through planning, gathering information through a number of evidences demonstrating the achievement of learning outcomes, reporting, and collecting information of the learning outcomes. In the implementation of classroom assessment, the roles of the teachers are very important in determining the accuracy of assessments to assess students’ success and failure. Types of the assessments designed should meet the standards of validity and reliability in order to achieve the results in accordance with what is expected. Therefore, the teachers’ professional competencies are essential requirement in assessing. In everyday life at school, it often appears assessment information that generates benefits both for teachers and students. In a class discussion, for example, the statements made by some students could be a guide for teachers to believe that students do not understand the concepts taught to them.